The Efficacy and Safety of Transarterial Chemoembolization Plus Iodine 125 Seed Implantation in the Treatment of Hepatocellular Carcinoma With Oligometastases: A Case Series Reports - Zhang, Weihua; Wu, Linxia; Chen, Lei; Ren, Yanqiao; Sun, Tao; Sun, Bo; Zhu, Licheng; Liu, Yiming; Zheng, Chuansheng (Frontiers in Oncology, 2022)
Background Patients with different primary tumor oligometastases can obtain survival benefits from external radiotherapy. The study was conducted to explore the efficacy and safety of transarterial chemoembolization (TACE) plus iodine 125 seed (TACE-I) implantation for hepatocellular carcinoma (HCC) oligometastases. Methods 187 patients who received TACE-I in our institution were retrospectively reviewed from January 2014 to December 2018. Thirty-two patients were included in the analysis. The primary endpoints of the study were overall survival (OS) and progression-free survival (PFS). The secondary endpoints of the study were tumor response and PFS of the metastatic sites. Results The median OS (mOS) of patients was 18 months, and the median PFS (mPFS) was 7 months. The objective response rate (ORR) and disease control rate (DCR) of patients three months after receiving TACE-I were 34.4% and 71.9%, respectively. The ORR and DCR of patients for metastatic sites were 50% and 81.3%, respectively. The mPFS of patients for metastatic sites was 14 months. The univariable and multivariable regression analyses indicated that the ECOG score was an independent predictor for mOS and mPFS. The number of iodine seeds and ECOG scores were independent predictors for mPFS for metastatic sites. After patients received TACE-I, the most common adverse events were abdominal pain, fever, and appetite. The adverse events of patients were relieved after receiving symptomatic treatments. Conclusion Iodine 125 seed implantation may be an effective and safe treatment for patients with hepatocellular carcinoma with oligometastasis, thereby providing a new selective option for these patients.